DETERMINATION OF SOURCES OF TURKS WITH TURKISH PROBLEMS IN GERMANY - Bülent KIRMIZI (Fırat University, 2019)
The Turks are the most important population of minorities living in Germany since 1960. Approximately three million people with such problems now been integrated into German society today and adaptation already left behind. The aim of the research, which the Turks left behind in Germany for half a century, is to determine to what extent they have in their daily lives Turkish. The questionnaire prepared for this purpose, by trying to determine thoughts and feelings about Turkey, the problems experienced native has sought to demonstrate that these factors play a role. Data are resident in Germany in 2014 with different socio-cultural level that was collected from 150 people. Turkish migration to Germany, the Federal Republic of Germany and Turkey begins with the labor agreement that we have signed on 30 October 1961 and 1 generation costs so that Turkish workers to Germany. Scroll to the day when this is no longer referred to the third generation. In the Turks in Germany themselves whether Turkey of course vary according to the person they felt foreign. The data obtained from the study, found that reveals the many doubts and concerns about the Turks living in Turkey in Germany. The first of these concerns is located in negative attitudes and behaviors towards them first-degree relatives in Turkey.